The Effect of Debt Financing, Equity Financing on Probability with Non-Performing Financing as an Intervening in Islamic Banking in Indonesia - Margaretha, Widya Wasti; Rahayu, Sri; Arum, Enggar Diah Puspa; Wiralestari, Wiralestari (PT FORMOSA CENDEKIA GLOBAL, 2024)
The banking industry is often considered the heart and driving force of a country's economy. This study to effect of debt financing, equity financing on profitability with non performing financing as an intervening. This study uses a quantitative research type using multiple linear regression analysis and path analysis as data analysis. The research sample was 9 banks in Islamic Banking in 2020-2023. The results of the study show that Debt Financing has a negative effect on ROA. Debt Financing has a positive effect on NPF. Equity Financing has a positive effect on ROA. Equity Financing has no effect on NPF. NPF has no effect on ROA.